The concept of time in the digital narrative of social media - Alasmari, Faiz S. (Frontiers in Human Dynamics, 2026)
The paper aims to philosophically explore the relationship between digital time and digital narrative. It explains two general topics. The first topic is the meaning of narrative as a literary genre. In addition, the paper seeks to formulate a different meaning of narrative depending on some philosophical thoughts. Then it explores the relationship between time and narrative. It concludes that narrative exists in time. Without time, narrative cannot live. Although language is important to narrative, it is merely a locator of where time is. The link between time and events is strong. An event is the only narrative component that embodies time. However, to have a philosophy of narrative as a carrier of the meaning of time and explanation of life and existence, narrative must be discussed as a philosophical way, not as a literary genre. The second general topic of the paper is about digital narrative and the digital concept of time. In this topic, narrative is not discussed as an independent topic; it links to several concepts, such as digital community and digital narrator. Some characteristics of digital media are explained to understand what this paper means by digital narrative. Narrative, understood as the carrier of meaning of time and the explainer of life and existence, exists by social media and within digital time, not by a human narrator. In digital narrative, several concepts drastically change. One or two aspects of interest can form a digital community. In addition, the past and the future do not exist on social media. Users live in unlimited ‘nows.’ This unlimited ‘now’ is shaped by the feature of permanence and continuity of social media, in which man’s engagement with social media has no end or limit.